RELATIONSHIP OF NUTRITION STATUS AND NUTRITIONAL ADEQUACY OF MORNING EATING WITH STUDENT ACHIEVEMENT OF SIDOMULYO 01 STATE ELEMENTARY SCHOOL STUDENTS WONOSALAM DISTRICT DEMAK REGENCY - Mulyadi Mulyadi; M. Zen Rahfiluddin; Dina Rahayuning Pangestuti (Jurnal Kesehatan Masyarakat (Undip), 2019)
The quality of human resources in all ages is influenced by various factors including school children. Nutritional status and health of school children will affect student achievement. In Indonesia, for children aged 5-12 years the short prevalence is 30.7%, in Central Java province, the short prevalence is 18% and very short 9%. This study aims to describe and analyze the Relationship between Nutritional Status and Nutritional Adequacy of Morning Meal with Student Achievement in Sidomulyo State Elementary School 01, Wonosalam District, Demak Regency.The method used in this study is quantitative with crossectional research design. The population in this study were grade 4 and 5 students at SD Negeri Sidomulyo 01 as many as 48 children. This study used a total sampling of 48 students. The variables in this study are learning achievement as a dependent variable and the independent variable is nutritional status and nutritional adequacy of breakfast. The data normality test uses kolmogrov smirnov with the result <0.05, the data is not normally distributed. Data analysis using the rank spearman test.The results showed that body mass index according to age (BMI / U), respondents had more normal nutritional status of 87.5%, adequate nutrition of breakfast less than 80% of the adequacy of the recommended breakfast. The average percentage of consumption of breakfast energy, protein, fat and carbohydrates for boys is 48.4%, 69.1%, 52.5%, and 43.7%. The average percentage of consumption of breakfast energy, protein, fat and carbohydrates for girls is 44.9%, 67.3%, 51.7%, and 38.5%. The average student's learning achievement is good (52.1%). There is no relationship between nutritional status and the nutritional adequacy of students' breakfast with learning achievement. Keywords: nutritional status, nutritional adequacy, students, learning achievement, elementary school